0
$\begingroup$

I would like to prove that (1) $$\begin{equation} \tan\left(\frac{\theta}{2}\right)=\tan\left(\frac{\nu}{2}\right)\tan\left(\frac{\pi/2-\epsilon}{2}\right) \end{equation}$$

can transformed to (2) $$x=y+z,$$ where (3) \begin{align} x&=&\mathrm{arctanh}\left(cos(\theta)\right)\\y&=&\mathrm{arctanh}\left(cos(\nu)\right)\\z&=&\mathrm{arctanh}\left(\sin\left(\epsilon\right)\right) \end{align}

By solving for $\theta$ in 1 and 2, we see that these are indeed equal:

enter image description here

For the record, incorrect identity

Initially the question was wrongly stated, and the comments below pertain to this: I would like to prove that (1) $$\begin{equation} \tan\left(\frac{\theta}{2}\right)=\tan\left(\frac{\nu}{2}\right)\tan\left(\frac{\pi/2-\epsilon}{2}\right) \end{equation}$$

can transformed to (2) $$x=y+z,$$ where (3) \begin{align} x&=&\mathrm{arctanh}\left(\theta\right)\\y&=&\mathrm{arctanh}\left(\nu\right)\\z&=&\mathrm{arctanh}\left(\sin\left(\epsilon\right)\right) \end{align}

My attempt on incorrect identity:

Taking the tanh of (2) on both sides and using $\begin{align} \tanh(x + y) &= \frac{\tanh x +\tanh y}{1+ \tanh x \tanh y } \end{align}$ results in (2a) $$\boxed{ \theta = \frac{\nu+\sin\left(\epsilon\right)}{1+\nu \sin\left(\epsilon\right)} }$$

On the other hand, using

\begin{align} \tan \frac{\theta}{2} &= \csc \theta - \cot \theta &= \pm\, \sqrt{1 - \cos \theta \over 1 + \cos \theta} &= \frac{\sin \theta}{1 + \cos \theta} &= \frac{1-\cos \theta}{\sin \theta} \end{align}

and $\sin(\pi/2-\epsilon)=\cos(\epsilon)$ and $\cos(\pi/2-\epsilon)=\sin(\epsilon)$ in (1) yields

$$\boxed{ \begin{equation} \tan\left(\frac{\theta}{2}\right)= \frac{\cos(\epsilon)(1-\cos(\nu))}{\sin(\nu)(1+\sin(\epsilon))} \end{equation} }$$ ... a bit stuck now

$\endgroup$
  • $\begingroup$ Did you tried starting with tag(y+z) and see if you could derive tag(x) based on the given relation? $\endgroup$ – Moti Dec 24 '15 at 20:04
  • $\begingroup$ Thank you, but I'm not getting very far. You are saying use tan(arctan) =.... but I dont quite see how this helps now. Otherwise, I know that $\tan(a)\tan(b)=\frac{\cos (A-B)-\cos (A+B)}{\cos (A-B)+\cos (A+B)}$, and that $\operatorname{artanh} \;u \pm \operatorname{artanh} \;v = \operatorname{artanh} \left( \frac{u \pm v}{1 \pm uv} \right)$, but I'm not sure what to follow this up with. $\endgroup$ – AimForClarity Dec 27 '15 at 7:44
  • $\begingroup$ I have a hard time seeing the connection between tan and arctanh here and why it has come up. $\endgroup$ – AimForClarity Dec 27 '15 at 7:47
  • $\begingroup$ I am not saying I know the answer - it requires some work. But start with $\tagh(y+z)$ (I made an error in my first comment), this will lead to a relation between the variables under the arc $\endgroup$ – Moti Dec 27 '15 at 18:34
  • $\begingroup$ Take a look at my attempt, maybe you have some further suggestions $\endgroup$ – AimForClarity Jan 5 '16 at 2:16
2
$\begingroup$

Answer to edited question

We'll begin by squaring your equation $(1)$ and invoking appropriate half-angle formulas:

$$\begin{align}\tan^2\frac{\theta}{2}= \tan^2\frac{\nu}{2}\tan^2\left(\frac{\pi}{4}-\frac{\epsilon}{2}\right) \qquad\to\qquad \frac{1-\cos\theta}{1+\cos\theta} &= \frac{1-\cos\nu}{1+\cos\nu}\cdot\frac{1-\cos\left(\frac{\pi}{2}-\epsilon\right)}{1+\cos\left(\frac{\pi}{2}-\epsilon\right)} \\[6pt] &= \frac{1-\cos\nu}{1+\cos\nu}\cdot\frac{1-\sin\epsilon}{1+\sin\epsilon} \end{align}$$ Thus, $$(1-\cos\theta)(1+\cos\nu)(1+\sin\epsilon) = (1+\cos\theta)(1-\cos\nu)(1-\sin\epsilon)$$ so that $$\begin{align} \cos\theta = \frac{\cos\nu + \sin\epsilon}{1+\cos\nu \sin\epsilon} &\quad\to\quad \tanh x = \frac{\tanh y + \tanh z}{1+\tanh y \tanh z}=\tanh(y+z) \\[6pt] &\quad\to\quad x = y+z \quad\square \end{align}$$


Answer to original question

Why do you think this relation is valid?

  • Certainly, if $\epsilon = 0$ (or $z = 0$), then (restricting domains appropriately) $\theta = \nu$ in (1), and $x = y$ in (2), which is consistent.

  • But if, say, $\nu = 0$, then (1) reduces to $\tan(\theta/2) = 0$, so that $\theta = 0$ and $x = 0$. However, $\epsilon$ ---and therefore also $z$--- is arbitrary in (1), whereas (2) requires $z = 0$.

Maybe you have some domain restrictions that avoid the second case, and lots of other numerical examples I could post. Let's look more generally.

Solving for $\theta$ in in terms of $\nu$ and $\epsilon$ in two ways, from (1) and (2)+(3), we find ourselves considering this statement: $$2\;\operatorname{atan}\left(\;\tan\frac{\nu}{2}\;\tan\left(\frac{\pi}{4} - \frac{\epsilon}{2}\right) \;\right) \;\stackrel{\text{?}}{=}\; \tanh\left(\;\operatorname{atanh}\nu + \operatorname{atanh} \sin\epsilon\;\right) \tag{$\star$}$$

Plots of the left- and right-hand sides appear here:

enter image description here

In the image (with $\nu$ and $\epsilon$ bounded by $0$ and $\pi/2$), we see that the plots do match when $\epsilon = 0$ and $\theta = \nu$, as discussed earlier. However, the plots quite clearly pull away from each other, showing a lack of equality for $\epsilon \neq 0$.

Therefore, we "almost-never" satisfy (1) and (2) simultaneously, so that $(\star)$ is not an identity.

$\endgroup$
  • $\begingroup$ That is true, there is a mistake in the equation that I was given. It doesn't make sense over the domain $\theta \in [0,\pi]$ and $\epsilon \in [0,\pi/2]$ $\endgroup$ – AimForClarity Jan 7 '16 at 4:36
  • $\begingroup$ I will edit my question above to clarify, I found the right relationship. Now, I have to prove it :) $\endgroup$ – AimForClarity Jan 7 '16 at 5:14

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.